Explosion impact strength calculation and failure analysis of glass fiber-reinforced composite pipe. Issue 19 (2nd October 2021) - Cao, Hanxue; Wang, Luhan; Wang, Chengcheng; Huang, Mengtao; Liu, Xi; Zeng, Qingwen; Zhang, Qianren; Zhong, Jingjun
Abstract: The investigation of failure analysis of the explosion impact strength of glass fiber-reinforced composite tubes was presented in this paper. Scanning electron microscopy was used to perform morphological observation and analysis of the failure cracks of a composite tube under ultra-high-pressure explosion impact. The main failure mode was brittle fiber fracture. Theoretical calculations and numerical simulations were used to analyze the deformation displacement and stress and strain of the composite tube under the impact of ultra-high pressure explosion. The boundary conditions obtained were 49.9 MPa as the minimum failure internal pressure and 0.0782 mm as the radial limit displacement.